DIGITAL SUBSTATION COMPONENT SYSTEM "SMART GRID" - V.I. Vasilchenko; O.G. Gryb; O.V. Leleka; D.A. Gapon; T.S. Ierusalimova (Electrical engineering & Electromechanics, 2014)
New production technologies of modern control systems have moved from the stage of research and experimentation into the stage of practical use. Modern communication standards for the exchange of information are developed and introduced. Digital devices, protectors and automation are widely used. There has been substantial development of hardware and software of control systems.